Nutritive value of fermented soybean grains for ruminants - de Carvalho, Laura Barbosa; da Costa, Ana Cláudia; Neta, Bárbara de Sousa Mota; Fonseca, Alessandra Schaphauser Roseto; Vieira, Karine Padilha Nunes [UNESP]; de Abreu, Matheus Lima Corrêa; e Pedreira, Bruno Carneiro; Galati, Rosemary Lais; Guerra, Wanderlei Dias; Cabral, Luciano da Silva (Springer Nature, 2023)
Fermented soybean grain (FSBG) is considered improper to use as a protein source in animal nutrition, since it is assumed that defects cause changes on its chemical composition and favor mycotoxins production, but chemical composition data does not support this theory and in vivo studies are missing. Thus, this study aimed to evaluate the effects of FSBG in feedlot lamb diets. For that, two types of FSBG (partially fermented and completely fermented, PFSBG and CFSBG) and one standard soybean grain (SSBG) were obtained and evaluated alone or as a component of experimental diets by in vitro and in vivo studies, where FSBG totally replaced SSBG in feedlot lamb diets, which was included in the experimental diets in 17.4% on dry matter basis as protein source. Before the studies, both soybeans were sent to a specialized laboratory where no mycotoxins were detected. As a result, lower DM and carbohydrate contents but higher crude protein, fiber, and indigestible NDF contents were measured in CFSBG than in SSBG. Furthermore, both types of FSBG showed lower digestibility in vitro dry matter (IVDMD) than SSBG when evaluated separately; however, when evaluated in experimental diets, the substitution of SSBG for FSBG did not affect IVDMD. It was also observed that FSBG also had less rumen-degradable protein than SSBG (mean 47.9 vs 86.4%). In the in vivo study, FSBG did not affect nutrient intake, apparent digestibility, or animal performance (i.e., average daily gain and carcass gain). Thus, mycotoxins-free FSBG may be an alternative to totally replace SSBG in feedlot lamb diets.
Keywords: Digestibility; Fermented soybean grain; In vitro evaluation; In vivo study; Lamb; Oilseeds